2019
DOI: 10.3847/1538-4357/ab0288
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Giant H ii Regions of the Milky Way with SOFIA. I. W51A

Abstract: We discuss the first results from our mid-infrared imaging survey of Milky Way Giant H II regions with our detailed analysis of W51A, which is one of the largest GH II regions in our Galaxy. We used the FORCAST instrument on SOFIA to obtain 20 and 37 µm images of the central 10 × 20 area, which encompasses both of the G49.5-0.4 and G49.4-0.3 sub-regions. Based on these new data, and in conjunction with previous multi-wavelength observations, we conjecture on the physical nature of several individual sources an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 86 publications
2
23
0
Order By: Relevance
“…Bisbas et al (2017) used radiative transfer calculations to show that the [CII] and CO lines show a significant offset in the process of the cloud collision. Such an offset is reported toward a few possible cloud-cloud collision sites (Bisbas et al 2018;Lim and De Buizer 2019). Nonetheless, it needs to be quantified how this signature differs from hierarchical gravitational collapse or feedback-driven outflows.…”
Section: High-mass Star Formation Triggered By Cloud-cloud Collisionsmentioning
confidence: 99%
“…Bisbas et al (2017) used radiative transfer calculations to show that the [CII] and CO lines show a significant offset in the process of the cloud collision. Such an offset is reported toward a few possible cloud-cloud collision sites (Bisbas et al 2018;Lim and De Buizer 2019). Nonetheless, it needs to be quantified how this signature differs from hierarchical gravitational collapse or feedback-driven outflows.…”
Section: High-mass Star Formation Triggered By Cloud-cloud Collisionsmentioning
confidence: 99%
“…Various studies of Galactic high mass star forming regions have found dust temperatures to be greater than ∼ 50 − 60 K (see e.g. Kraemer et al 2001;Barbosa et al 2016;Lim & De Buizer 2019). This also applies to higher resolution observations of Arp 220 by Wilson et al (2014), among others, who derived average dust temperatures of 80 K and 197 K for the eastern and western nuclei, respectively.…”
Section: Expanding the Calculations Of Van Der Walt (2014)mentioning
confidence: 65%
“…Moreover, since Class I YSOs are associated with dense molecular clouds, it would be harder for the blast wave to plow the dense gas, and instead, the shock wave would slow down where we observe both Class I and II YSOs at the boundary regions between HB 3 and W3 Complex. One needs to bear in mind that the comparison of separate evolutionary tracers of such SF activities, e.g., virial parameter (α vir ) vs. luminosity -mass ratio (L/M ) (Lim & De Buizer 2019) or unambiguous identification of YSOs with follow-up spectroscopy is still needed to support our conclusion.…”
Section: Objectsmentioning
confidence: 95%